A Semantic Concast service for data discovery, aggregation and processing on NDN. (1st January 2019) - Liao, Zhuhua; Teng, Zengde; Zhang, Jian; Liu, Yizhi; Xiao, Hao; Yi, Aiping
Abstract: Offering a flexible paradigm for intelligently discovering, aggregating and processing big distributed data is a crucial requirement in large content-centric Internet. However, the major hindrances to this paradigm are network's dynamic feature, traffic balance, wired forwarding and the absence of cooperation between communications and computations. In this paper, we present a scalable Semantic Concast service on Named Data Networking (NDN) being considered as a promising paradigm for the future Internet. The service enables cooperation between data discovering, aggregating and processing among intermediate nodes for a user's Interest that contained a hierarchical name and semantic constraints. Specifically, multiple types and strategies of data aggregation and processing for combining and processing the positive data and suppressing the negative, futile data, as well as a determination of response completeness are introduced for enhancing relevant results recall and sharing. The experimentation demonstrated the Semantic Concast service can effectively improve service quality, reduce network traffic and shorten response time.